Electrochemical Studies of WC-Flyash HVOF Coating Interface on SA209-T1 Steel under 3.5 NaCl Solution. (9th November 2021) - Elango, D.; Daniel Das, A.; Kumaresh Babu, S. P.; Natarajan, S.; Yeshitla, A.
Abstract : In this present research, the coatings of SA209-T1 using high velocity oxygen fuel were employed for the application of boiler tubes. Due to the adaptation of corrosion easy in boiler material, the research of those properties is significant because of its criticality and functionality during the service time. A right coating was found and applied on the SA209-T1 surface against corrosive environments. Good corrosion resistance is achieved by WC-flyash coatings applied on SA209-T1 substrate. The 90% WC-10% flyash coatings were found to be more protective followed by SA209-T1 steel. WC-flyash covering was tracked down so that the covering is compelling to secure the SA209-T1 steel substrate. It is reasoned that the arrangement of NiO, Cr2 O3, CoO, and NiCr2 O4 could add to the advancement of consumption opposition in coatings. The steel of uncoated endured erosion as extraordinary stripping and spalling of the scale, which could be because of the development of Fe2 O3 oxide scale unprotectively. This paper reveals the performance, applications, and development of 90wt.% WC and 10wt.% fly ash through HVOF coating in SA209-T1 for electrochemical corrosion studies at room temperature.